Computerised ultrasound image guidance for automated prostatectomy - Liu, Yuan Jie. (2009)
A semi-automatic method for intraoperative sizing and 3D reconstruction of the prostate, using transrectal or transurethral ultrasound images, for automated prostatectomy is proposed. Based on prostate capsule boundaries drawn out by the surgeon manually or delineated automatically by the computer algorithm, a 3D model of the prostate is reconstructed within which the cutting sequence to achieve a barrel shape cavity, confined within the 3D model of the reconstruction, can be developed. A 3D model of the prostate can be displayed on the screen by means of an oblique projection.